2022
DOI: 10.3389/fonc.2021.810023
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib in Combination With Endocrine Therapy for Patients With Hormone Receptor-Positive, HER2-Negative Metastatic Breast Cancer: A Phase 1b Study

Abstract: BackgroundCyclin-dependent kinases (CDK) 4 and 6 regulate G1 to S cell cycle progression and are often altered in cancers. Abemaciclib is a selective inhibitor of CDK4 and CDK6 approved for administration on a continuous dosing schedule as monotherapy or as combination therapy with an aromatase inhibitor or fulvestrant in patients with advanced or metastatic breast cancer. This Phase 1b study evaluated the safety and tolerability, pharmacokinetics, and antitumor activity of abemaciclib in combination with endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For the patients with detectable PIK3CA mutations in ctDNA (002, 006 008 and 011) a PIK3CA inhibitor may have indicated as detailed in the SOLAR-1 trail [21]. Alternatively, CDK4/6 inhibitor abemaciclib plus fulvestrant could be used regardless of PIK3CA or ESR1 mutation status [22]. Furthermore, it is possible that combining eribulin with CDK4/6 inhibitor could be an effective treatment strategy in overcoming resistance to CDK4/6 inhibitors, speci cally to block the escaped cells that pass the G1/S cell cycle phase irrespective of the CDK4/6 inhibitor treatment [23].…”
Section: Resultsmentioning
confidence: 99%
“…For the patients with detectable PIK3CA mutations in ctDNA (002, 006 008 and 011) a PIK3CA inhibitor may have indicated as detailed in the SOLAR-1 trail [21]. Alternatively, CDK4/6 inhibitor abemaciclib plus fulvestrant could be used regardless of PIK3CA or ESR1 mutation status [22]. Furthermore, it is possible that combining eribulin with CDK4/6 inhibitor could be an effective treatment strategy in overcoming resistance to CDK4/6 inhibitors, speci cally to block the escaped cells that pass the G1/S cell cycle phase irrespective of the CDK4/6 inhibitor treatment [23].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which simeprevir and tamoxifen combination therapy leads to a reduced tumor burden, and reduced HER2 expression, is currently unknown, and may necessitate further study. Additionally, many studies have shown the benefit of aurora kinase inhibitors, as well as other cell cycle inhibitors, in combination with antiestrogens [ 57 , 58 , 59 ]. Although both tamoxifen and aurora kinase inhibitors are cytostatic, to our knowledge, this is the first study to identify the additional benefit of reduction in HER2 upregulation provided by combination therapy when compared to tamoxifen monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…When the aromatase enzyme is blocked, estrogen production is ceased. When compared to tamoxifen, aromatase inhibitors (AIs) lower the risk of recurrence in postmenopausal women with ER-positive breast cancer [110]. Anastrozole and letrozole are reversible aromatase inhibitors that compete with one another to block the enzyme.…”
Section: Ribociclibmentioning
confidence: 99%